Altered prefrontal signaling during inhibitory control in a salient drug context in cocaine use disorder. (4th March 2022) - Ceceli, Ahmet O; Parvaz, Muhammad A; King, Sarah; Schafer, Matthew; Malaker, Pias; Sharma, Akarsh; Alia-Klein, Nelly; Goldstein, Rita Z
Abstract: Introduction: Drug addiction is characterized by impaired response inhibition and salience attribution (iRISA), where the salience of drug cues is postulated to overpower that of other reinforcers with a concomitant decrease in self-control. However, the neural underpinnings of the interaction between the salience of drug cues and inhibitory control in drug addiction remain unclear. Methods: We developed a novel stop-signal functional magnetic resonance imaging task where the stop-signal reaction time (SSRT–a classical inhibitory control measure) was tested under different salience conditions (modulated by drug, food, threat, or neutral words) in individuals with cocaine use disorder (CUD; n  = 26) versus demographically matched healthy control participants ( n  = 26). Results: Despite similarities in drug cue-related SSRT and valence and arousal word ratings between groups, dorsolateral prefrontal cortex (dlPFC) activity was diminished during the successful inhibition of drug versus food cues in CUD and was correlated with lower frequency of recent use, lower craving, and longer abstinence ( Z  > 3.1, P  < 0.05 corrected). Discussion: Results suggest altered involvement of cognitive control regions (e.g. dlPFC) during inhibitory control under a drug context, relative to an alternative reinforcer, in CUD. Supporting the iRISA model, these results elucidate the direct impact of drug-related cue reactivity on the neural signature of inhibitory control in drug addiction.